Clustering and exploring university students’ knowledge and attitude toward energy sustainability - Divya Chandrasenan; Reshma John Kuleenan; Vaisakh Yesodharan; Annie Feba Varghese (Energy Reports, 2022)
An investigation of the attitudes and understanding of Indian university students, who are considered the country’s future workforce, was conducted to see if they could be classified into subgroups depending on their energy attitudes. The surveyed population was divided into four unique “personas”, each with a different level of engagement and a different perception of energy, using Hierarchical Cluster analysis. “Agents of Change”, “Mindful wanderer”, “Big talker”, and “Indifferent onlooker” were the four clusters identified. Energy knowledge was studied for fundamental energy themes, and the correlation test found a substantial positive relationship between energy knowledge and a person’s energy attitude. It also investigates how the findings on subgroups or personas can influence the construction of energy education curricula at different educational levels.